School – family relations: Greek parents’ perceptions of parental involvement - Poulou, Maria (International Journal about Parents in Education, 2023)
While the value of the school-family partnership is universally accepted, it is not always easy to promote effective parent-teacher partnership. A central question that emerges is how schools can ensure that they develop their home-school relationship in a way that acknowledges the needs and perspectives of children, parents and teachers and enhances parents’ participation in school activities. Our main assumption is that we can better understand school-family relations, by examining the beliefs held by both teachers and parents about their relationship. This study addressed Greek parents’ perceptions of teachers, as well as their own role and responsibilities, parental involvement activities and areas of cooperation with teachers. Analysis of 581 questionnaires to parents revealed that parents perceived distinctly separate roles between teachers and parents. Teachers were perceived as “experts” in academic domains, while parents were perceived as “guardians” of children’s social and emotional growth. Both teachers and parents’ role was to keep each other informed about children’s achievement in school and home setting respectively. Results of the study are discussed in terms of implications for initiatives to develop school-family relations in teacher training programmes.